2014
DOI: 10.1111/mms.12136
|View full text |Cite
|
Sign up to set email alerts
|

Population size and migratory connectivity of humpback whales wintering in Las Perlas Archipelago, Panama

Abstract: From 2003 to 2009, we surveyed Las Perlas Archipelago off the Pacific coast of Panama 53 times between the months of August and October to estimate abundance of humpback whales and to test for a migratory connection with populations from the southern hemisphere. We identified 295 individuals using photo-identification of dorsal fins, including 58 calves, and the population estimate for a single season was 100-300 solitary adults plus 25-50 mothers with calves; the estimated population of animals across all sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…, Guzmán et al . ), and provide the first evidence that the whales that summer in the Antarctic Peninsula migrate to northern Peru. However, our main focus was to provide new insights into the spatial structuring of BSG humpback whales by testing the hypothesis of potential latitudinal preferences in their migratory behavior.…”
Section: Discussionmentioning
confidence: 84%
“…, Guzmán et al . ), and provide the first evidence that the whales that summer in the Antarctic Peninsula migrate to northern Peru. However, our main focus was to provide new insights into the spatial structuring of BSG humpback whales by testing the hypothesis of potential latitudinal preferences in their migratory behavior.…”
Section: Discussionmentioning
confidence: 84%
“…The eastern South Pacific humpback whale population or breeding Stock G (International Whaling Commission ) is distributed along neritic waters from northern Peru (∼4°S) to Costa Rica (∼12°N) with known breeding sites of concentration in northern Peru (Guidino et al ), Ecuador (Scheidat et al , Félix et al ), Colombia (Flórez‐González ), Panama (Rasmussen et al , Guzman et al ), and southeastern Costa Rica (Rasmussen et al ). The stock has ≥3 summer destinations for feeding, particularly in the Patagonia Fjords, the Magellan Strait, the Corcovado Gulf in Chile, and the Gerlache Strait (64°30′S, 62°20′W) in western Antarctic Peninsula (Gibbons et al , Stevick et al , Acevedo et al , Hucke‐Gaete et al ).…”
Section: Study Areamentioning
confidence: 99%
“…Thus, an apparent relationship would exist between whale abundance and latitude. Whale abundance peaks off Panama in August and September (Guzmán et al, 2015) and off Colombia in August (Flórez-González et al, 1998); while off Ecuador, it is reported in July (Scheidat et al, 2000;Félix & Haase, 2001). In northern Peru, the peak is observed towards the end of the breeding season in September and October (Pacheco et al, 2009;Santillán, 2011;Guidino et al, 2014).…”
mentioning
confidence: 99%
“…However, residence patterns and movements within the breeding region may vary within and between seasons (Baker & Herman, 1981;Calambokidis et al, 2001;Smith et al, 2012;Guzmán et al, 2015). Understanding the movement patterns within the breeding area may provide valuable information about the migration timing and habitat use by whales along the breeding grounds (e.g., Guzmán & Félix, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation